2023
DOI: 10.1111/cts.13591
|View full text |Cite
|
Sign up to set email alerts
|

Totality of evidence of the effectiveness of repurposed therapies for COVID‐19: Can we use real‐world studies alongside randomized controlled trials?

Abstract: Rapid and robust strategies to evaluate the efficacy and effectiveness of novel and existing pharmacotherapeutic interventions (repurposed treatments) in future pandemics are required. Observational ‘Real‐World Studies’ (RWS) can report more quickly than randomised controlled trials (RCTs) and would have value were they to yield reliable results. Both RCTs and RWS were deployed during the COVID‐19 pandemic. Comparing results between them offers a unique opportunity to determine the potential value and contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Mandema et al. 8 performed a retrospective comparison of real‐world studies (RWS) and randomized controlled trials (RCTs) from eight treatment regimens for COVID‐19 to determine a rapid an robust strategy for drug repurposing in future pandemics. The comparison showed that the focus should be on large well‐conducted RCTs.…”
mentioning
confidence: 99%
“…Mandema et al. 8 performed a retrospective comparison of real‐world studies (RWS) and randomized controlled trials (RCTs) from eight treatment regimens for COVID‐19 to determine a rapid an robust strategy for drug repurposing in future pandemics. The comparison showed that the focus should be on large well‐conducted RCTs.…”
mentioning
confidence: 99%